Penerapan Radio Frequency Identification (RFID) Untuk Efisiensi Inventaris Pada Toko Minimal - Irma Tiara; Binastya Anggara Sekti (Ikatan Ahli Informatika Indonesia, 2024)
Minimal is a local Indonesian fashion brand which is famous for its minimalist and modern designs. Minimal's main store is located at Kota Kasablanka Mall, LG Floor, Jl. Casablanca Raya Kav. 88, South Jakarta. Problems arise from inefficient inventory management, such as stock inaccuracies, difficulties in product tracking, and the length of the inventory process. This has a negative impact on the store, including lost potential sales and decreased customer satisfaction. At a minimum, we also don't have an integrated system to manage inventory in real-time across all branches. The aim of this research is to implement an RFID (Radio Frequency Identification) system to increase inventory management efficiency and improve customer service. RFID is a technology that uses radio waves to identify and track objects automatically. Research methods include needs analysis, system design, RFID implementation, and performance evaluation. The results of implementing the RFID system at Minimal stores show a significant increase in inventory accuracy by 98%, a reduction in inventory time by 75%, and an increase in customer satisfaction by 30%.